2012
DOI: 10.1007/s11099-012-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses of Caragana korshinskii Kom. under extreme drought stress: Leaf abscission and stem survives

Abstract: Caragana korshinskii Kom. is a perennial xerophytic shrub, well known for its ability to resist drought. In order to study ecophysiological responses of C. korshinskii under extreme drought stress and subsequent rehydration, diurnal patterns of gas exchange and chlorophyll (Chl) fluorescence parameters of photosystem II as well as Chl content were analyzed. Plant responses to extreme drought included (1) leaf abscission and using stem for photosynthesis, (2) improved instantaneous water-use efficiency, (3) dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Several stresses can lead cell death and leaf abscission in plants, like drought [ 61 , 62 ] and salt [ 63 ] stresses. Hence, we analyzed the transcripts involved in the response to stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Several stresses can lead cell death and leaf abscission in plants, like drought [ 61 , 62 ] and salt [ 63 ] stresses. Hence, we analyzed the transcripts involved in the response to stresses.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon suggests that plant conducting tissue becomes more developed under reduced precipitation 44 . Recent research has shown that C. korshinskii can accumulate more carbohydrates in its stems and branches in response to extreme drought stress, and such changes are necessary for new leaves to re-sprout and re-grow 45 .…”
Section: Discussionmentioning
confidence: 99%
“…S. psammophila is important to the energy and paper industries, whereas C. korshinskii is economically important as a highly productive forage shrub. Effects of the short-term drought on seedling water relations and photosynthesis on these two species have been studied (Liu et al, 2007;Xu et al, 2012), but little is known about the responses of mature plants to the long-term drought and varied precipitation. Thus, we conducted a manipulated experiment with three levels of precipitation (a control with ambient precipitation, 50% above ambient precipitation (irrigation treatment), and 50% below ambient precipitation (drought treatment)) on these two shrubs to address the following three questions: (1) are A n and g s higher in C. korshinskii than in S. psammophila under severe drought due to the anisohydric behavior of C. korshinskii and isohydric behavior of S. psammophila (Li et al, 2016)?…”
Section: Introductionmentioning
confidence: 99%
“…(2) does the shallow-rooted S. psammophila respond more strongly than C. korshinskii to the higher precipitation, and is it severely inhibited under drought treatment? and (3) xeric species photosynthetically acclimate to the long-term drought better than riparian species (Martin-StPaul et al, 2012;Zhou et al, 2016), so does the drought-resistant C. korshinskii (Ma et al, 2008;Xu et al, 2012) photosynthetically acclimate better than the drought-vulnerable S. psammophila?…”
Section: Introductionmentioning
confidence: 99%